PENERAPAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA SISWA KELAS II SEKOLAH DASAR - mahbubah, fitriyatul (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract: The Application of Realistic Mathematics Education (RME) Approach in Improving Mathematics Learning at The Second Grade Students. The objectives of this study are: to describe the steps of application of RME approach in Mathematics learning, learning improvement of Mathematics learning by implementing RME approach, and to describe problems and solutions in the application of RME approach. This research is collaborative Classroom Action Research (CAR) conducted in three cycles, consisting of planning, implementation, observation, and reflection on each cycle. The subject of this research was 27 students. Techniques of collecting data were observation, anecdotal record, and test. The conclusion of this research is the application of RME approach carried out with the right steps can improve Mathematics learning outcomes at the second grade students of SDN 1 Kedungwinangun in the academic year of 2014/2015. Keywords: RME approach, learning improvement, Mathematics Abstrak: Penerapan Pendekatan Pendidikan Matematika Realistik (PMR) dalam Peningkatan Pembelajaran Matematika Siswa Kelas II Sekolah Dasar. Tujuan penelitian ini adalah: untuk mendeskripsikan langkah-langkah penerapan pendekatan PMR, peningkatan pembelajaran matematika dengan menerapkan pendekatan PMR, dan (3) mendeskripsikan kendala dan solusi penerapan pendekatan PMR. Penelitian Tindakan Kelas (PTK) kolaboratif ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Subyek pada penelitian ini berjumlah 27 siswa. Teknik pengumpulan data berupa observasi, anecdotal record, dan tes. Simpulan penelitian ini adalah penerapan pendekatan PMR dapat meningkatkan pembelajaran matematika tentang bangun datar siswa kelas II SDN 1 Kedungwinangun tahun ajaran 2014/2015. Kata Kunci : Pendekatan PMR, Peningkatan Pembelajaran, Matematika